The history of corruption in central government = L'histoire de la corruption au niveau du pouvoir central - Tiihonen, Seppo (Cahier d'histoire de l'administration, 2003)
This work is a study of administrative corruption from an historical perspective. It aims to answer questions such as :Can we find general patterns in the development of corruption? And what are the connections between administrative corruption, political corruption and development?